Global Bounds for Cocoercive Variational Inequalities - Fan Jianghua; Wang Xiaoguo (Abstract and Applied Analysis)
By using the strong monotonicity of the perturbed fixed-point map and the normal map associated with cocoercive variational inequalities, we establish two new global bounds measuring the distance between any point and the solution set for cocoercive variational inequalities.